Link between Geographical Origin and Occurrence of Brucella abortus Biovars in Cow and Water Buffalo Herds - Borriello, Giorgia (American Society for Microbiology, 2013)
Sixty-three Brucella isolates from water buffaloes and cattle slaughtered within the Italian national plan for brucellosis control were characterized by multiple-locus variable-number tandem repeat analysis (MLVA). Genotyping indicated a strong influence of geographic origin on the Brucella abortus biovar distribution in areas where brucellosis is endemic and highlighted the importance of rigorous management procedures aimed at avoiding inter- and intraherd spreading of pathogens.